2021
DOI: 10.3390/en14030751
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized PV Control System Based on the Emperor Penguin Optimizer

Abstract: During the day, photovoltaic (PV) systems are exposed to different sunlight conditions in addition to partial shading (PS). Accordingly, maximum power point tracking (MPPT) techniques have become essential for PV systems to secure harvesting the maximum possible power from the PV modules. In this paper, optimized control is performed through the application of relatively newly developed optimization algorithms to PV systems under Partial Shading (PS) conditions. The initial value of the duty cycle of the boost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Full optimization is required when the PV system is under dynamic partial shading patterns. A relatively new optimization algorithm, Emperor Penguin Optimizer (EPO), has been developed [34] . Another new optimization method called Cuttlefish Algorithm (CFA) for partial shading is proposed in [35] to enhance the performance of the PV system.…”
Section: Introductionmentioning
confidence: 99%
“…Full optimization is required when the PV system is under dynamic partial shading patterns. A relatively new optimization algorithm, Emperor Penguin Optimizer (EPO), has been developed [34] . Another new optimization method called Cuttlefish Algorithm (CFA) for partial shading is proposed in [35] to enhance the performance of the PV system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CFA may also exhibit slow convergence in dynamic or rapidly changing environmental conditions, such as solar irradiance variations or partial shading, which can negatively impact its MPPT performance. Similarly, in [23], a new MPPT control technique using emperor penguin optimizer (EPO) is evaluated under changing irradiance levels and partial shading conditions. However, like CFA, EPO may also have limitations in terms of convergence speed due to the movement of penguin agents, which can be slower compared to other optimization algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively, deterministic algorithms such as P&O and InC, directly calculate the optimal operating point based on a mathematical model, while metaheuristic algorithms explore the solution space iteratively to find the optimal operating point [20]. Metaheuristic algorithms such as particle swarm optimization (PSO) [21], JAYA [21], adaptive‐JAYA (AJAYA) [1], cuttlefish algorithm (CFA) [22], and emperor penguin optimizer (EPO) [23] have been suggested for optimizing the parameters of the boost converter used in MPPT. Their goal is to enhance the likelihood of reaching the GMPP.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the fuzzy logic based Integral (I) controller has lower overshoot and settling time than the classical PI controller. Particle swarm optimization (PSO), harmony search algorithm, cuttlefish algorithm, and emperor penguin optimizer are proposed to optimize parameters of the PI controller in an MPPT system [13][14][15][16]. The results show that these techniques succeed in improving the transient performance of the area frequency and the power in the tie line.…”
Section: Introductionmentioning
confidence: 99%